Dark matter in the Local Group - Kudrya, Yu.N.; Tsykaliuk, Iu.Iu. (Advances in Astronomy and Space Physics, 2014)
The observational properties of galaxies aumulated in the Updated Nearby Galaxy Catalog (UNGC) were used by us to derive an orbital mass of the Milky Way and Andromeda galaxy (M 31) via motions of their 31 and 39 ompanions, respe tively. The ratio of the orbital mass of galaxies, whih is a measure of dark matter, to their stellar mass is ∼ 30. If this value is taken as the average value in the Universe, then in the standard
osmologial ΛCDM models it will math the value Ωm ≈ 0.09 instead of the generally a epted value Ωm ≈ 0.28. Taking into aount that this last value is realised only in rih lusters, and that the luster at hand ontains only 10% of the total number of galaxies (while the rest are in groups or field galaxies), our results on firm the well-known problem of "lak of dark matter" in the Loal group.